The PI3K/AKT/mTOR pathway in breast cancer: targets, trials and biomarkers. (July 2014) - Paplomata, Elisavet; O'Regan, Ruth
The phosphoinositide 3 kinase (PI3K)/Akt/mammalian (or mechanistic) target of rapamycin (mTOR) pathway is a complicated intracellular pathway, which leads to cell growth and tumor proliferation and plays a significant role in endocrine resistance in breast cancer. Multiple compounds targeting this pathway are being evaluated in clinical trials. These agents are generally well tolerated and can be used in combination with targeted therapies, endocrine therapy or cytotoxic agents. The identification of subtypes of tumors more likely to respond to these therapeutics cannot be overemphasized, since breast cancer is a very heterogeneous malignancy. Activation of pathways such as KRAS and MEK can act as escape mechanisms that lead to resistance, thus a combination of agents targeting multiple steps of the intracellular machinery is promising. There is evidence that tumors with PIK3CA mutations are more sensitive to inhibitors of the PI3K pathway but this has yet to be validated. Large clinical trials with correlative studies are necessary to identify reliable biomarkers of efficacy.